GAMBARAN MOTIVASI BELAJAR SISWA DI MASA PANDEMI COVID-19 (Pada Siswa Kelas XII SMAN 1 Sukatani) - Sita Mellinia Yulinaria; Maya Masyita Suherman (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
The Covid-19 virus is a virus that was originally found in China and has now spread to various regions, especially the State of Indonesia. This condition certainly has an impact on students' learning motivation, because students think they are bored and bored with online learning conditions. The purpose of this study is to find out a description of the motivation or encouragement of learning for class XII students at SMA Negeri 1 Sukatani during the covid-19 outbreak. This study uses a qualitative descriptive system. The data collection methods that I used in this study were interviews and documentation. The results prove that the study conducted on the four students at SMA Negeri 1 Sukatani still has the motivation to learn in the category of having student goals or aspirations; learning capacity; physical and spiritual condition; the condition of the student; dynamic factors of learning; teacher's efforts to teach students.Keywords: Covid-19, Motivation of Learning